Development of Pedagogical Professional Competency for Muhammadiyah Elementary School Teachers - Sunariati, Rintik; Muhibbin, Ahmad; Anif, Sofyan; Prayitno, Harun Joko (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research describes the pedagogical professional competency development program for Muhammadiyah Elementary School teachers as PSP Class 1. The study aims to outline a program aimed at enhancing professional pedagogical competencies in elementary schools, focusing on the development of teachers' professional pedagogical competence. This research employs a descriptive qualitative approach. The data sources include interviews conducted with five school principals and thirty-seven teachers. Data collection techniques involve interviews, observations, field notes, and documentation. The study's findings reveal that the pedagogical competency development program at Muhammadiyah Elementary School in Klaten Regency is deemed satisfactory. The school administration organizes various teacher competency development programs, including the Teacher Working Group (KKG). These programs and training activities encompass several aspects such as enhancing teachers' educational insights, curriculum development, improving understanding towards students, implementing effective and logical teaching methods, developing proficiency in lesson planning, utilizing ICT for teaching and learning purposes, and enhancing teachers' abilities in utilizing nature-based teaching methods and conducting student assessments. Several supporting factors contribute to the development of teachers' pedagogical competence in Muhammadiyah elementary schools. The driving factors behind these initiatives include support from internal school structures such as learning committees, study groups, colleagues, school psychologists, parents, foundations, and the government. The programs are tailored to meet the specific needs and conditions in the field, thereby supporting school activities as implementers of School Mobilization Force 1. Furthermore, pedagogical competency development activities necessitate a carefully planned and staged approach to ensure effectiveness and sustainability.